AIDS Health Promotion Exchange. (Geneva Amsterdam : WHO Global Programme on AIDS Royal Tropical Institute, 1988)
Fonds Suzan Daniel (FSD)
Periodiciteit: driemaandelijks
Redactie: WHO/GPA, 1211 Geneva 27; vanaf (1992) Mauritskade 63, 1092 AD Amsterdam
VA Sexual Health Exchange
Engels
Periodiek